Rancang Bangun Sistem Pemetaan Kesenian Garut Berbasis Web - Nuraisah, Siti; Cahyana, Rinda (Institut Teknologi Garut, 2025)
Distinctive arts and local community culture as cultural heritage inherited from generation to generation, traditional art is present as a window to the local wisdom of ancestors, this art has various forms such as dance, music, theater, fine arts, to literature. The Garut Regency Culture and Tourism Office stated that traditional art information facilities still use book media, the renewal of this information system aims to map the arts in Garut Regency which is still considered ineffective for this digital era. Furthermore, the purpose of this research is to produce a web-based Garut Traditional Arts mapping system. In analyzing and designing this mapping system, the Rational Unified Process (RUP) method is used with several stages, namely Inception, Elaboration, Construction, Transition and for modeling using Unified Modelling Langguange (UML). The system was tested using the blackbox testing method. The Garut art location mapping system by applying Leaflet to display traditional art locations. This research results in a Garut art mapping system that can provide information on locations, facilities and activities as promotional media.